Coworking as a model for conscious business. Issue 3 (15th August 2019) - Orel, Marko; Kubátová, Jaroslava
Abstract : Purpose: The purpose of this paper is to cross-reference the defining perspectives of coworking as an emerging integral model of conscious business. Design/methodology/approach: The methodological framework is built on transdisciplinary research of spatial scale of existence by using the qualitative approach of participant observations and interviews. Findings: The empirical data suggest that independently organized and self-financed coworking spaces can be categorized as conscious businesses. Research limitations/implications: Coworking spaces are evolving and hybridizing. While a conscious business model can be cross-referenced with independently run coworking spaces that target the self-employed as their user group, this is not certain for larger, franchise-based coworking centers as a larger sample would need to be researched and analyzed. Originality/value: No attempts have been made previously for identifying cross-references between the concept of conscious business and the coworking model.